COMPARATIVE STUDY OF BIOACTIVE COMPOUNDS IN MILK THISTLE SEED VARIETIES IN SULAIMANI, IRAQ - Rozhgar M. A.; B. J. Mahmood; A. J. Muhammad rashid; K. R. Ahmad (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was conducted using two different varieties of milk thistle, var. marianum, and var. albiflorum. The plant samples were collected from the Sulaimani region to determine silymarin content, bioactive constituents, and antioxidant activity. HPLC analysis showed that var. marianum contains a high amount of silymarin (365.680±3.815 mg/g). Silybin B, Silychristin A, and Silybin A were the major flavonolignans in these varieties—the var. marianum contains silybins B, silychristin A, and silybin A (174.880±6.495, 86.720±2.113, and 54.960±2.483 mg/g) respectively. The hexane extract analysis of milk thistle seeds of the marianum and albiflorum varieties identified 26 (95.229±1.318) and 19 (94.547±6.541) phytochemical compounds, respectively. Both varieties contain a higher amount of oleic acid, which was found to be 14.800±0.481 and 31.940±0.726 in both varieties, respectively. This study evaluates the scavenging effect of milk thistle plants using a DPPH assay. The result indicated that the var. marianum had a maximum scavenging effect of 72.944% compared to the var. albiflorum, (61.846%). The stronger IC50 was obtained by var. marianum with 17.027±0.064 µg/mL.